Evaluation of Arabic Listening Tests Based on The CEFR Framework: Level Classification and Competency Indicators: Evaluasi Tes Menyimak Bahasa Arab Berdasarkan Kerangka CEFR: Klasifikasi Level dan Indikator Kompetensi - Anisa Pitri Ramadani; Ihwan Mahmudi; Tiara Eki Wahyu Rinawati; Syakira Esa Rahimi Sari; Andi Nurizzah Aqilah; Nima Chusna Umniyah (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2025)
Listening comprehension is one of the most challenging components of Arabic language learning due to auditory limitations, environmental distractions, and the rapid and non-repeatable nature of spoken language. To support the development of more standardized listening assessments, this study aims to analyze and classify 29 types of Arabic listening test items based on the Common European Framework of Reference for Language(CEFR). Using a descrptive-qualitative approach, data were collected through literature review and document analysis of 29 test types found in al-ikhtibarat al-lughawiyyah. The findings reveal that these test types can be systematically mapped across the six CEFR proficiency levels (A1-C2), each reflecting distinct competency indicators ranging from basic word recognition to the interpretation of implicit meaning in complex spoken discourse. The result also demonstrate that the test variations cover a broad spectrum of listening abilities, offering a representative model for CEFR-aligned listening assessment in Arabic. This study contributes a practical classification framework that can serve as a reference for educators and test developers in designing more objective, transparent, and proficiency-oriented listening evaluations. Practically, this framework enables teachers to select, adapt, and construct listening test items that better align with learners’ proficiency profiles and support more effective instruction and assessment of Arabic listening skills. Keywords: Arabic Listening Skills, CEFR, Competency Indicators, Language Assessment, Test Design